Foam films, heat shrinkable films, and labels
Patent Information
- Application Number
- JP2023505572
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2021-03-08
- Filing Date
- 2022-03-08
- Publication Date
- 2025-03-07
- Estimated Expiration
- 2042-03-08
Smart Images

Figure 0007642057000005 
Figure 0007642057000001 
Figure 0007642057000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a foamed film, a heat shrinkable film, and a label. [Background technology]
[0002] Labels are used for PET bottled beverages and the like, and there is a demand for improving the recyclability of PET bottles by improving the separability between the bottle and the label. Patent Document 1 discloses a label that uses a foam film as a label that can be separated underwater. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4813181 Summary of the Invention [Problem to be solved by the invention]
[0004] However, when printing is performed on the surface of a foamed film, surface smoothness becomes an issue.
[0005] The present invention has been made in view of the above problems, and provides a foamed film having excellent surface smoothness and a low specific gravity. The present invention also provides a heat-shrinkable film and a label using the foamed film, which have excellent surface smoothness even after stretching. [Means for solving the problem]
[0006] According to the present invention, (1) there is provided a foamed film having a foamed layer and a non-foamed layer, wherein the first resin composition constituting the foamed layer contains one or more block copolymers having a vinyl aromatic hydrocarbon monomer unit and a conjugated diene monomer unit, and has a melt mass flow rate of 5.0 to 15.0 g / 10 min at 200°C and a load of 5 kg, and the second resin composition constituting the non-foamed layer contains one or more block copolymers having a vinyl aromatic hydrocarbon monomer unit and a conjugated diene monomer unit, and has a melt mass flow rate of 2.0 to 7.0 g / 10 min at 200°C and a load of 5 kg, and the specific gravity of the foamed film is 0.8 or more and less than 1.0. In this specification, the tilde symbol "~" is a symbol used to indicate a numerical range including the numerical values written before and after it. Specifically, the description "X to Y" (X and Y are both numerical values) indicates "X or more and Y or less".
[0007] Various embodiments of the present invention will be described below. The embodiments described below can be combined with each other. Preferably, (2) The foamed film according to (1), wherein the melt mass flow rate of the first resin composition at 200° C. under a load of 5 kg is greater than the melt mass flow rate of the second resin composition at 200° C. under a load of 5 kg. (3) The foamed film according to (1) or (2), wherein the first resin composition and / or the second resin composition has a conjugated diene monomer unit content of 10 to 40 mass%, when the total of the vinyl aromatic hydrocarbon monomer unit and the conjugated diene monomer unit in each composition is 100 mass%. (4) A heat-shrinkable film using the foamed film according to any one of (1) to (3). (5) A label using the foamed film according to any one of (1) to (3) or the heat-shrinkable film according to (4). [Brief description of the drawings]
[0008] [Figure 1]1A to 1C are schematic diagrams showing examples of the laminated structure of a foamed film. Fig. 1A is an example of a foamed film having a non-foamed layer on both sides of a foamed layer. Fig. 1B is an example of a foamed film having a non-foamed layer on one side of a foamed layer. Fig. 1C is an example of a foamed film having a non-foamed layer on a foamed layer via another layer. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] Hereinafter, embodiments of the present invention will be described. Various features shown in the following embodiments can be combined with each other. Also, each feature can be an invention independently.
[0010] 1. Foam film The foamed film according to one embodiment of the present invention includes a foamed layer and a non-foamed layer. The foamed film may include a plurality of foamed layers and non-foamed layers. The foamed film may include a layer other than the foamed layer and the non-foamed layer. It is preferable that at least one non-foamed layer is used as a surface layer.
[0011] 1A to 1C are schematic diagrams showing examples of the laminated structure of a foamed film. FIG. 1A is an example of a foamed film having a non-foamed layer provided on both sides of a foamed layer. FIG. 1B is an example of a foamed film having a non-foamed layer provided on one side of a foamed layer. FIG. 1C is an example of a foamed film having a non-foamed layer provided on a foamed layer via another layer. The non-foamed layer can be provided directly on the foamed layer or via another layer.
[0012] Here, the other layer may be an intermediate layer composed of one or more layers. The other layer may be an undercoat layer, for example, an adhesive layer capable of bonding layers together.
[0013] The total thickness of the foamed film is preferably 30 to 200 μm, and more preferably 50 to 150 μm.
[0014] The thickness of the foamed layer in the foamed film is preferably 20 to 190 μm, more preferably 30 to 140 μm. When the thickness is 20 μm or more, a film with a low specific gravity is easily obtained, and when the thickness is 190 μm or less, wrinkles are unlikely to occur during processing or when the film is attached to a container as a label, and a film with good appearance is obtained, which is preferable.
[0015] There is no particular restriction on the layer ratio (ratio of thickness of each layer) of the multilayer film, but it is preferable that the non-foamed layer is 75% or less of the total thickness in order to obtain a foamed film with a low specific gravity, and it is preferable that the non-foamed layer is 5% or more in order to obtain good surface smoothness.
[0016] 1A is a three-layer structure foamed film in which a non-foamed layer 3 and a non-foamed layer 4 are provided on both sides of a foamed layer 1. In such a film, when the thickness of the non-foamed layer 3 is d1, the thickness of the foamed layer 1 is d2, and the thickness of the non-foamed layer 4 is d3, the ratio thereof [d1 / d2 / d3] is, for example, [1 / 38 / 1] to [1 / 1 / 1], and preferably [1 / 5 / 1] to [1 / 1 / 1].
[0017] The specific gravity of the foamed film is 0.8 or more and less than 1.0, preferably 0.82 to 0.95. By setting it in such a range, a foamed film with excellent surface smoothness and low specific gravity can be provided. By setting it to 0.8 or more, a film with good surface smoothness can be obtained, and by setting it to less than 1.0, it is possible to separate the film with a specific gravity of 1.0 or more by specific gravity separation with water, which is preferable.
[0018] The foam layer is a layer formed of a first resin composition. The first resin composition contains one or more block copolymers having vinyl aromatic hydrocarbon monomer units and conjugated diene monomer units.
[0019] The first resin composition has a melt mass flow rate (first MFR) of 5.0 to 15.0 g / 10 min at 200° C. and a load of 5 kg, preferably 8.0 to 14.0 g / 10 min, and more preferably 10.0 to 14.0 g / 10 min. By adjusting the MFR to within such a range, a foamed film having a surface smoothness suitable for printing can be obtained. The first MFR is specifically, for example, 5.0, 6.0, 7.0, 8.0, 9.0, 10.0, 11.0, 12.0, 13.0, 14.0, or 15.0 g / 10 min, and may be within a range between any two of the numerical values exemplified here.
[0020] In addition, when the total amount of the vinyl aromatic hydrocarbon monomer units and the conjugated diene monomer units in the first resin composition is taken as 100 mass%, the content of the conjugated diene monomer units is preferably 10 to 40 mass%, and more preferably 15 to 30 mass%.
[0021] The non-foamed layer is a layer constituted by a second resin composition. The second resin composition contains one or more block copolymers having vinyl aromatic hydrocarbon monomer units and conjugated diene monomer units.
[0022] The second resin composition has a melt mass flow rate (second MFR) of 2.0 to 7.0 g / 10 min at 200° C. and a load of 5 kg, preferably 4.0 to 6.0 g / 10 min. By adjusting the second MFR to within such a range, a foamed film having excellent film-forming properties and surface smoothness suitable for printing can be obtained. The second MFR is specifically, for example, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6.0, 6.5, or 7.0 g / 10 min, and may be within a range between any two of the numerical values exemplified here.
[0023] In addition, in the second resin composition, when the total of the vinyl aromatic hydrocarbon monomer units and the conjugated diene monomer units in the composition is taken as 100 mass%, the content of the conjugated diene monomer units is preferably 10 to 40 mass%, more preferably 15 to 30 mass%.
[0024] The block copolymer contained in the first resin composition or the second resin composition is a block copolymer having a vinyl aromatic hydrocarbon monomer unit and a conjugated diene monomer unit. The block copolymer is a copolymer synthesized by block copolymerizing a vinyl aromatic hydrocarbon monomer and a conjugated diene monomer. The block copolymer is a copolymer having one or more types of block chains constituted by vinyl aromatic hydrocarbon monomer units and / or conjugated diene monomer units.
[0025] The vinyl aromatic hydrocarbon monomer unit is a structural unit of the copolymer derived from the vinyl aromatic hydrocarbon monomer used in block copolymerization. Examples of the vinyl aromatic hydrocarbon monomer include styrene, o-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, 2,5-dimethylstyrene, α-methylstyrene, vinylnaphthalene, and vinylanthracene. In one embodiment, the vinyl aromatic hydrocarbon monomer is preferably styrene. These monomers may be used alone or in combination of two or more.
[0026] The conjugated diene monomer unit is a structural unit of the copolymer derived from the conjugated diene monomer used in block copolymerization. Examples of the conjugated diene monomer include 1,3-butadiene, 2-methyl-1,3-butadiene (isoprene), 2,3-dimethyl-1,3-butadiene, 1,3-pentadiene, and 1,3-hexadiene. In one embodiment, the conjugated diene monomer is preferably 1,3-butadiene or isoprene. These monomers may be used alone or in combination of two or more.
[0027] The overall structure of the block copolymer and the structure of the polymer blocks constituting the block copolymer are not particularly limited. The structure of the polymer block may be a polymer block mainly composed of vinyl aromatic hydrocarbon monomer units (e.g., styrene units), a polymer block mainly composed of conjugated diene monomer units (e.g., 1,3-butadiene units), a polymer block having a random structure in which vinyl aromatic hydrocarbon monomer units (e.g., styrene units) and conjugated diene monomer units (e.g., 1,3-butadiene units) are randomly arranged, or a polymer block having a tapered structure in which vinyl aromatic hydrocarbon monomer units (e.g., styrene units) and conjugated diene monomer units (e.g., 1,3-butadiene units) are arranged in a tapered state with a gradient in the distribution density. The overall structure of the block copolymer has at least two or more types of polymer blocks. There are no particular limitations on the type of polymer block or the order in which the polymer blocks are linked. The polymer blocks may be linked in a linear manner, or in a branched or star-shaped manner. For example, a polymer block having a random structure containing styrene units and 1,3-butadiene units can be obtained by simultaneously and continuously adding small amounts of styrene and 1,3-butadiene to the polymerization active terminals and polymerizing them. For example, a polymer block having a tapered structure containing styrene units and 1,3-butadiene units can be obtained by simultaneously and collectively adding excess amounts of styrene and 1,3-butadiene to the polymerization active terminals and polymerizing them. Furthermore, the overall structure of the block copolymer can be made branched or star-shaped by using a multifunctional initiator or coupling agent.
[0028] The number average molecular weight of the block copolymer is preferably 40,000 to 500,000, more preferably 80,000 to 300,000. By making it 40,000 or more, the block copolymer composition can have sufficient rigidity and impact resistance, and by making it 500,000 or less, the block copolymer composition can have good processability, which is preferable. The number average molecular weight of the block copolymer can be measured using a gel permeation chromatograph (hereinafter abbreviated as GPC).
[0029] The melt mass flow rate of the first resin composition at 200° C. and a load of 5 kg is greater than the melt mass flow rate of the second resin composition at 200° C. and a load of 5 kg. In other words, it is preferable to satisfy the relationship "first MFR>second MFR".
[0030] The method for producing a block copolymer according to an embodiment of the present invention is not particularly limited, but may be, for example, a method for polymerizing the vinyl aromatic hydrocarbon monomer and the conjugated diene monomer in an organic solvent using an organolithium compound as an initiator.
[0031] Examples of the organic solvent include aliphatic hydrocarbons such as butane, pentane, hexane, isopentane, heptane, octane, and isooctane; alicyclic hydrocarbons such as cyclopentane, methylcyclopentane, cyclohexane, methylcyclohexane, and ethylcyclohexane; and aromatic hydrocarbons such as benzene, toluene, ethylbenzene, and xylene.
[0032] An organolithium compound is a compound having one or more lithium atoms bonded to the molecule. Examples of the organolithium compound include monofunctional organolithium compounds such as ethyllithium, n-propyllithium, isopropyllithium, n-butyllithium, sec-butyllithium, and tert-butyllithium, and polyfunctional organolithium compounds such as hexamethylenedilithium, butadienyldilithium, and isoprenyldilithium.
[0033] In so-called living anionic polymerization using an organolithium compound as an initiator, the vinyl aromatic hydrocarbon and the conjugated diene subjected to the polymerization reaction can be almost entirely converted into a polymer.
[0034] The molecular weight of the polymer is controlled by the amount of the organolithium compound added, and a polymer satisfying the target melt mass flow rate can be obtained by adjusting the amount of the organolithium compound added. Also, a mixture satisfying the target melt mass flow rate can be obtained by melt mixing a plurality of resins.
[0035] A randomizer may be added to control the polymerization state. Tetrahydrofuran (THF) is mainly used as the randomizer, but other ethers, amines, thioethers, phosphoramide, alkylbenzenesulfonate, potassium or sodium alkoxide, etc. can also be used. Suitable ethers include dimethyl ether, diethyl ether, diphenyl ether, diethylene glycol dimethyl ether, diethylene glycol dibutyl ether, etc., in addition to THF. As amines, tertiary amines such as trimethylamine, triethylamine, tetramethylethylenediamine, and cyclic amines can also be used. Other randomizers that can be used include triphenylphosphine, hexamethylphosphoramide, potassium or sodium alkylbenzenesulfonate, potassium or sodium butoxide, etc.
[0036] The amount of the randomizer to be added may be, for example, 0.001 to 10 parts by mass per 100 parts by mass of the total monomer charge. The addition may be made before the start of the polymerization reaction or before the polymerization of the copolymer chain. In addition, the randomizer may be additionally added as necessary.
[0037] The block copolymer thus obtained is inactivated by adding a polymerization terminator such as water, alcohol, carbon dioxide, etc., in an amount sufficient to inactivate the active terminals. The copolymer can be recovered from the obtained block copolymer solution by any method, such as (A) a method of precipitating with a poor solvent such as methanol, (B) a method of precipitating by evaporating the solvent with a heated roll or the like (drum dryer method), (C) a method of concentrating the solution with a concentrator and then removing the solvent with a vented extruder, or (D) a method of dispersing the solution in water, blowing in steam to heat and remove the solvent, and recovering the copolymer (steam stripping method).
[0038] The first resin composition or the second resin composition can be obtained by mixing at least one type of block copolymer obtained by the above-mentioned production method or the like, and, if necessary, other additives.
[0039] Examples of other additives include various stabilizers, lubricants, processing aids, antiblocking agents (antiblocking agents), antistatic agents, antifogging agents, light resistance improvers, softeners, plasticizers, pigments, etc. Each additive may be added to the block copolymer solution, or may be blended with the recovered copolymer and melt-mixed.
[0040] Examples of the stabilizer include phenol-based antioxidants such as 2-tert-butyl-6-(3-tert-butyl-2-hydroxy-5-methylbenzyl)-4-methylphenyl acrylate, 2-[1-(2-hydroxy-3,5-di-tert-pentylphenyl)ethyl]-4,6-di-tert-pentylphenyl acrylate, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and 2,6-di-tert-butyl-4-methylphenol, and phosphorus-based antioxidants such as trisnonylphenyl phosphite. Examples of the antiblocking agent, antistatic agent, and lubricant include fatty acid amide, ethylene bisstearamide, sorbitan monostearate, saturated fatty acid ester of fatty alcohol, and pentaerythritol fatty acid ester. It is preferable to use these additives in an amount of 5% by mass or less based on the block copolymer.
[0041] The first resin composition or the second resin composition may contain two or more block copolymers, and a known method can be adopted as a method for mixing these block copolymers. For example, they may be dry-blended using a Henschel mixer, a ribbon blender, a super mixer, a V blender, or the like, and may be melted and pelletized using an extruder. In one embodiment, melt mixing is preferred. Alternatively, a method of mixing polymer solutions together and then removing the solvent can be used.
[0042] The method for producing the foamed film is not particularly limited, but for example, a method of forming a foamed layer and a non-foamed layer by co-extruding the first resin composition and the second resin composition can be used. In this case, the resin compositions constituting the other layers may be extruded together. The foamed film may also be produced by extruding each layer one by one or several layers together, and then laminating them.
[0043] The method for forming the foam layer is not limited, and generally used methods can be used, such as a chemical foaming method in which a resin is foamed by a gas generated by thermal decomposition of a chemical foaming agent when the resin and the chemical foaming agent are melt-kneaded, and a physical foaming method in which a gas is injected into a molten resin in an extruder to foam the resin.
[0044] Specific examples of chemical foaming agents used in the chemical foaming method include organic acids such as sodium bicarbonate, citric acid, azodicarbonamide, azobisisobutyronitrile, diazoaminobenzene, N,N'-dinitrosopentamethylenetetraamine, N,N'-dimethyl-N,N'-dinitroterephthalamide, benzenesulfonyl hydrazide, p,p'-oxybisbenzenesulfonyl hydrazide, carbonates, and the like, and two or more of these may be mixed and used. Sodium bicarbonate or a mixture of sodium bicarbonate and sodium citrate is preferably used, and the foaming gas generated is carbon dioxide gas. There is no particular limitation on the method of adding the chemical foaming agent, but any of the following may be used: a method of dry blending with resin pellets, a method of adding using a quantitative feeder in the hopper of an extruder, or a method of preparing and adding a master batch (foaming agent master batch) based on the same resin as the main raw material. The amount of the chemical foaming agent added is appropriately adjusted depending on the desired expansion ratio and the amount of gas generated by the foaming agent.
[0045] Specific examples of physical foaming agents used in the physical foaming method include carbon dioxide gas, propane, butane, n-pentane, dichlorodifluoromethane, dichloromonofluoromethane, trichloromonofluoromethane, methanol, ethanol, water, etc., but carbon dioxide gas is preferably used in terms of safety. Examples of methods for adding the physical foaming agent include a method of feeding the agent to the central zone of an extruder or the central zone of a first-stage extruder when a tandem extruder is used. Alternatively, resin pellets impregnated with a foaming gas may be fed into an extruder to obtain a foamed film. The amount of the physical foaming agent added is appropriately adjusted depending on the desired expansion ratio.
[0046] 2.Heat shrinkable film A heat shrinkable film according to one embodiment of the present invention is a film using the above-mentioned foamed film. The heat shrinkable film is the above-mentioned foamed film (heat shrinkable foamed film) that has been stretched. The specific gravity of the foamed film hardly changes even when stretched. However, due to the presence of bubbles in the foam layer, the stress distribution during stretching is not necessarily uniform, and the smoothness of the original foamed film tends to decrease. A heat shrinkable film according to one embodiment of the present invention is a heat shrinkable film that maintains a surface smoothness suitable for printing even after stretching.
[0047] In one embodiment, the heat-shrinkable film may be produced by stretching each layer and then laminating them. The lamination method may be a general method such as a method using an adhesive or a method using heat, but if the temperature is too high, the heat-shrinkable film will shrink, which is not preferable. There is no particular limit to the lamination temperature, but the preferred temperature range is less than 70°C. In another embodiment, the heat-shrinkable film may be produced by stretching a foamed film, which is a multilayer film after co-extrusion or lamination. In this specification, the terms "sheet" and "film" are not used to distinguish between different thicknesses, but when the thickness changes (becomes thinner) by an operation such as stretching, the film before it becomes thinner may be called a "sheet".
[0048] The stretching may be uniaxial, biaxial or multiaxial. Examples of uniaxial stretching include a method of stretching an extruded foam sheet in a direction perpendicular to the extrusion direction (TD direction) with a tenter, a method of stretching an extruded tubular foam film in a circumferential direction, and a method of stretching an extruded foam sheet in the extrusion direction (MD direction) with a roll. Examples of biaxial stretching include a method of stretching an extruded foam sheet in the extrusion direction (MD direction) with a roll and then stretching in a direction perpendicular to the extrusion direction (TD direction) with a tenter or the like, and a method of stretching an extruded tubular foam film in the extrusion direction and the circumferential direction simultaneously or separately.
[0049] The stretching temperature is preferably, for example, 60 to 120°C. A temperature of 60°C or higher makes the film less likely to break during stretching, and a temperature of 120°C or lower is preferable because a film having good shrinkage properties can be obtained. Particularly preferred is a temperature range of Tg+5°C to Tg+20°C with respect to the glass transition temperature (Tg) of the composition constituting the film. In the case of a multilayer film, a temperature range of Tg+5°C to Tg+20°C with respect to the Tg of the polymer composition of the layer having the lowest Tg is particularly preferred. The glass transition temperature (Tg) can be determined, for example, from the temperature at the peak of the loss modulus.
[0050] The stretching ratio is not particularly limited, but is preferably 1.5 to 8 times. A stretching ratio of 1.5 times or more can provide a film with good shrinkage properties, and a stretched film can be easily produced by stretching the film to 8 times or less, which is preferable. In one embodiment, the heat shrinkage ratio of the heat shrinkable film is preferably 65% or more at 100°C for 10 seconds. When the heat shrinkable film is used as a heat shrinkable label or packaging material, the heat shrinkage ratio is preferably 10% or more at 70°C for 10 seconds. When the heat shrinkage ratio is 10% or more, the temperature does not need to be high during shrinkage, so that the influence on the article to be covered can be suppressed. A preferred heat shrinkage ratio is 15% or more at the same temperature. In one embodiment, the heat shrinkage ratio is preferably 65% or more at 100°C for 10 seconds. In one embodiment, the natural shrinkage ratio is preferably 2.5% or less at 40°C for 7 days.
[0051] The total thickness of the heat shrinkable film is preferably 30 to 200 μm, and more preferably 50 to 150 μm.
[0052] 3.Other The foamed film and the heat-shrinkable film can be used as labels, cap seals, and other packaging materials.
[0053] A heat-shrinkable label using a heat-shrinkable film as a label can be produced by a known method, for example, by printing a stretched film, and then solvent-sealing the film so that the stretched direction is the circumferential direction. Alternatively, the label can be produced by laminating a printed heat-shrinkable label to a non-stretched foam film, and then solvent-sealing the film so that the direction of large shrinkage is the circumferential direction.
[0054] The labels can be used, without particular limitation, as labels for metal can containers made of tinplate, TFS, aluminum, etc. (three-piece cans and two-piece cans, or bottle cans with lids, etc.), glass containers, or resin containers made of polyethylene terephthalate (abbreviated as PET) or polyethylene, etc.
[0055] In addition, foamed films and heat-shrinkable films, especially heat-shrinkable labels, have a specific gravity of less than 1. Therefore, when used as labels for PET bottles, they can be separated from the container underwater, which has the advantage of being highly recyclable. EXAMPLES
[0056] The present invention will be described in more detail below with reference to examples. Note that these are merely illustrative and do not limit the scope of the present invention.
[0057] [Preparation of block copolymer: P-1] (1) 250.0 kg of cyclohexane and 35.0 g of tetrahydrofuran (THF) were placed in a reaction vessel. (2) 960 mL of a 10% by mass solution of n-butyllithium in cyclohexane was added thereto as a polymerization initiator solution, and the temperature was maintained at 30°C. (3) 17 kg of styrene was added and the styrene was polymerized anionically. The internal temperature rose to 72°C. (4) After the styrene was completely consumed, the internal temperature of the reaction system was lowered to 30°C, and 60 kg of styrene and 23 kg of 1,3-butadiene were added simultaneously in one batch. The internal temperature rose to 100°C. (5) After styrene and 1,3-butadiene were completely consumed, all polymerization active ends were finally quenched with water to obtain a polymerization solution containing a block copolymer having a polystyrene block and a tapered block of styrene and butadiene. (6) This polymerization solution was pre-concentrated and then extruded with a twin-screw extruder equipped with a vacuum vent to remove volatile components, thereby obtaining the desired block copolymer (P-1) in the form of pellets.
[0058] <Number average molecular weight> The number average molecular weight was measured by GPC under the following conditions. Device name: HLC-8220GPC (Tosoh Corporation) Column: Four Shodex GPCKF-404 columns (Showa Denko K.K.) were connected in series. Temperature: 40℃ Detection: UV-Visible spectroscopy (254 nm) Solvent: Tetrahydrofuran Concentration: 2% by mass Calibration curve: Prepared using standard polystyrene (VARIAN).
[0059] [Preparation of block copolymer: P-2] (1) 250.0 kg of cyclohexane and 35.0 g of tetrahydrofuran (THF) were placed in a reaction vessel. (2) 1,120 mL of a 10% by mass solution of n-butyllithium in cyclohexane was added thereto as a polymerization initiator solution, and the temperature was maintained at 30°C. (3) 4 kg of styrene was added and the styrene was polymerized anionically. The internal temperature rose to 62°C. (4) After the styrene was completely consumed, the internal temperature of the reaction system was raised to 80°C, and while maintaining the internal temperature, 53 kg of styrene and 13 kg of 1,3-butadiene were added simultaneously at constant addition rates of 53 kg / h and 13 kg / h, respectively. (5) After styrene and 1,3-butadiene were completely consumed, the internal temperature of the reaction system was lowered to 75°C, and 10 kg of 1,3-butadiene was added all at once to carry out anionic polymerization of 1,3-butadiene. The internal temperature rose to 83°C. (6) After 1,3-butadiene was completely consumed, the internal temperature of the reaction system was lowered to 70°C, 20 kg of styrene was added, and styrene was polymerized anionically. The polymerization was continued while cooling the reaction vessel to remove the reaction heat. The internal temperature rose to 90°C. (7) After the styrene was completely consumed, all of the polymerization active ends were finally quenched with water to obtain a polymerization liquid containing a block copolymer having a polystyrene block, a random block of styrene and butadiene, a polybutadiene block, and a polystyrene block. (8) This polymerization liquid was pre-concentrated and then extruded in a twin-screw extruder equipped with a vacuum vent to remove volatile components and form pellets, thereby obtaining block copolymer P-2.
[0060] [Preparation of block copolymer: P-3] A block copolymer P-3 was obtained in the same manner as in P-2, except that 670 mL of a 10 mass % cyclohexane solution of n-butyllithium was added as the polymerization initiator solution.
[0061] [Preparation of block copolymer: P-4] A block copolymer P-4 was obtained in the same manner as in P-1, except that 1340 mL of a 10 mass % cyclohexane solution of n-butyllithium was added as the polymerization initiator solution.
[0062] [Preparation of block copolymer: P-5] A block copolymer P-5 was obtained in the same manner as in P-1, except that 540 mL of a 10 mass % cyclohexane solution of n-butyllithium was added as the polymerization initiator solution.
[0063] [Preparation of block copolymer: P-6] (1) 250.0 kg of cyclohexane and 35.0 g of tetrahydrofuran (THF) were placed in a reaction vessel. (2) 590 mL of a 10% by mass solution of n-butyllithium in cyclohexane was added thereto as a polymerization initiator solution, and the temperature was maintained at 30°C. (3) 20 kg of styrene was added and the styrene was polymerized anionically. The internal temperature rose to 73°C. (4) After the styrene was completely consumed, the internal temperature of the reaction system was lowered to 30°C, and 38 kg of styrene and 42 kg of 1,3-butadiene were added simultaneously in one batch. The internal temperature rose to 100°C. (5) After styrene and 1,3-butadiene were completely consumed, all polymerization active ends were finally quenched with water to obtain a polymerization solution containing a block copolymer having a polystyrene block and a tapered block of styrene and butadiene. (6) This polymerization solution was pre-concentrated and then extruded with a twin-screw extruder equipped with a vacuum vent to remove volatiles, thereby obtaining the desired block copolymer in the form of pellets (P-6).
[0064] [Preparation of block copolymers: P-7] (1) 250.0 kg of cyclohexane and 35.0 g of tetrahydrofuran (THF) were placed in a reaction vessel. (2) 630 mL of a 10% by mass solution of n-butyllithium in cyclohexane was added thereto as a polymerization initiator solution, and the temperature was maintained at 30°C. (3) 30 kg of styrene was added and the styrene was polymerized anionically. The internal temperature rose to 79°C. (4) After the styrene was completely consumed, the internal temperature of the reaction system was raised to 80°C, and while maintaining the internal temperature, 31 kg of styrene and 9 kg of 1,3-butadiene were added simultaneously at constant addition rates of 31 kg / h and 9 kg / h, respectively. (5) After styrene and 1,3-butadiene were completely consumed, the internal temperature of the reaction system was lowered to 70°C, 30 kg of styrene was added, and styrene was polymerized anionically. The polymerization was continued while cooling the reaction vessel to remove the reaction heat. The internal temperature rose to 93°C. (6) After the styrene was completely consumed, all of the polymerization active ends were finally quenched with water to obtain a polymerization liquid containing a block copolymer having a polystyrene block, a random block of styrene and butadiene, a polybutadiene block, and a polystyrene block. (7) This polymerization solution was pre-concentrated and then extruded in a twin-screw extruder equipped with a vacuum vent to remove volatile components and form pellets, obtaining block copolymer P-7. Table 1 shows the conditions under which block copolymers P-1 to P-7 were prepared.
[0065] [Table 1]
[0066] [Composition adjustment: SBC-A to SBC-I] According to the formulations in Table 2, the copolymers were melt-kneaded as necessary to prepare compositions SBC-A to SBC-I.
[0067] [Melt mass flow rate measurement] The melt mass flow rates (MFR) of the obtained compositions SBC-A to SBC-I were measured in accordance with JIS K7210. However, the second resin composition of the non-foamed layer also contains an antiblocking agent, and the melt mass flow rates are values measured using samples prepared by melt-kneading 100 parts by mass of each of compositions SBC-A, SBC-C, SBC-D, SBC-E, and SBC-F with the antiblocking agent in the prescribed ratios shown in Tables 3 and 4. Device name: No.120-LABOT Melt Flow Index Tester (Yasuda Seiki Seisakusho) Temperature: 200℃ Load capacity: 5kg Die: Standard die
[0068] [Table 2]
[0069] [Example 1] A method for producing the heat shrinkable film (heat shrinkable foam film) of Example 1 will be described below.
[0070] The heat shrinkable foam film of Example 1 was produced by the method described below. For convenience of explanation, the second layer of the heat shrinkable film according to this embodiment is referred to as the front and back layers (when referring to only one, it is referred to as the front or back layer), the first layer is referred to as the inner layer, and the manufacturing process of the heat shrinkable foam film is described by dividing it into (1) extrusion of the front and back layers, (2) extrusion of the inner layer, and (3) sheet (film) stretching.
[0071] (1) Sheet extrusion of the front and back layers Using an extruder equipped with a multi-layer T-die with a lip width of 300 mm capable of extruding two-kind three-layer sheets, a second resin composition was extruded into a sheet, which was prepared by melt-mixing 100 parts by mass of a block copolymer of SBC-A as the front and back layers and 1.3 parts by mass of a product name "E640N" (manufactured by Toyo Styrene Co., Ltd.) as the antiblocking agent, according to the mass ratio shown in Table 3. The extruder that melts the resin for the front and back layers and supplies it to the multi-layer die was a single-screw extruder with a diameter of 40 mm, and the set temperature was 200°C. The set temperature of the multi-layer T-die was 190°C.
[0072] (2) Sheet extrusion of the inner layer The inner layer was co-extruded simultaneously with the extrusion of the front and back layers described in (1) using the block copolymer of SBC-D (first resin composition) and 0.6 parts by mass of the product name "Polysrene ES405" (manufactured by Eiwa Chemical Industry Co., Ltd.) as the foaming agent master batch (foaming agent MB). Polysrene ES405 contains sodium bicarbonate, and the amount of sodium bicarbonate in 0.6 parts by mass was 0.24 parts by mass. The extruder for the resin for the inner layer was a single-screw extruder of 65 mmφ, and the set temperature was 200°C. By using an extruder equipped with a multi-layer T-die, the front and back layers described in (1) and the inner layer described in (2) were discharged from the multi-layer T-die as a laminated sheet of two types of three layers in close contact with each other. At the inlet of the extruder, the block copolymer of SBC-D is in a state of dry blending 91 parts by mass of pellets of the block copolymer of P-2 and 9 parts by mass of pellets of the block copolymer of P-3, but both pellets are melt-mixed in the extruder and supplied to the multi-layer die. The multi-layer T-die was set at a temperature of 190° C. The mass ratio of SBC-A (second resin composition) and SBC-D (first resin composition) supplied to the surface layer, inner layer, and back layer was 1 / 2 / 1. The thickness of the obtained laminated sheet (foamed film) was 0.30 mm, and since foaming occurred in the inner layer, the thickness ratio of the surface layer, inner layer, and back layer was 1 / 3 / 1.
[0073] (3) Stretching of the laminated sheet The obtained laminated sheet, a foamed film, was passed through a longitudinal stretching machine having two rolls with different rotation speeds at 80°C so as not to be stretched in the MD direction (i.e., the stretching ratio was 1.0 times), and then passed through a tenter-type transverse stretching machine to be stretched 4.5 times in the TD direction at 90°C, finally obtaining a 70 μm-thick heat-shrinkable foamed film of Example 1.
[0074] In Examples 2 to 9 and Comparative Examples 1 to 5, films were formed under the conditions shown in Tables 3 and 4 in the same manner as in Example 1.
[0075] <Specific gravity>
[0076] The specific gravity of the heat shrinkable foamed film was measured by cutting a test piece from the foamed film and using the test piece in accordance with the "submerged weighing method" of JIS Z8807:2012 using the device shown below. Device name: MD-200S (Alpha Mirage) If the specific gravity of the heat shrinkable foam film is in the range indicated by "Excellent", it indicates that the specific gravity is sufficiently low, and it is judged to be effective in solving the problem of the present invention. Even if the specific gravity is in the range indicated by "Good", it is judged to be at a level that can solve the problem of the present invention. However, if the specific gravity is in the range indicated by "Poor", it is judged to be unable to solve the problem of the present invention. Excellent: Specific gravity <0.92 Good: 0.92≦specific gravity<0.97 Impossible: 0.97≦specific gravity
[0077] <Surface roughness> Using a device named "Surfcorder ET4000" (manufactured by Kosaka Laboratory), three-dimensional surface roughness measurements (i.e., measurements of surface smoothness) were carried out in an area of 1 mm x 0.5 mm. For the evaluation, only a reference length (L) was extracted in the direction of the average line from the roughness curve obtained by scanning the film in the MD direction, and the x-axis was taken in the direction of the average line of this extracted portion and the y-axis was taken in the direction of the longitudinal magnification. When the roughness curve was expressed as y = f(x), the absolute value of f(x) was integrated in the range from 0 to L and divided by L to obtain the arithmetic average surface roughness (Ra). The measurement results were evaluated according to the following criteria. That is, if the arithmetic mean surface roughness (Ra) of the heat shrinkable foamed film is in the range indicated as "excellent", it indicates that there is no particular problem with the printability on the film surface, and it is judged to be effective in solving the problem of the present invention. Even if it is in the range indicated as "good", it is judged to be at a level that can solve the problem of the present invention. However, if the value of Ra is in the range indicated as "poor", printing is hindered, and it is judged that the problem of the present invention cannot be solved. Excellent: Ra<0.3μm Good: 0.3≦Ra≦0.4 Impossible: 0.4 <Ra
[0078] <Heat shrinkage rate> The heat shrinkage rate at 100°C was calculated by immersing the stretched film (heat shrinkable foamed film) in warm water adjusted to 100°C for 10 seconds and using the following formula. Heat shrinkage rate (%) = (L1-L2) / L1 x 100 L1: Length before shrinkage (in the main stretch (TD) direction) L2: Length after shrinkage (in the main stretch (TD) direction) The calculated heat shrinkage rate was evaluated according to the following criteria. If the heat shrinkability rate was evaluated as "excellent" or "good," it was determined that the film had the heat shrinkage rate, which is a basic characteristic of a heat shrinkable film, and was therefore suitable for practical use. Excellent: 70%<Heat shrinkage rate Good: 60%≦Heat shrinkage rate≦70% Not acceptable: Heat shrinkage rate <60%
[0079] <Water separation> The heat-shrinkable foam film and the PET bottle were cut into 1 cm squares, placed in water and stirred, and left to stand for 1 minute, after which the state of separation was evaluated. Excellent: The foam film piece and the PET bottle piece were completely separated into upper and lower parts in the water. Unacceptable: The foam film piece and the PET bottle piece are not separated partially or completely in the water.
[0080] <Film forming properties> The film-forming property was evaluated according to the following criteria. If the film-forming property was evaluated as "excellent" or "good", it was possible to produce a heat-shrinkable foamed film. Excellent: Good film-forming properties Good: Film formation is possible, but the following defects (*1) to (*3) may occur in film formation. *1: The foam is not stable. *2: FE (fish eye: foreign matter caused by poor mixing, etc.) is on the rise *3: May break Not possible: Film cannot be formed.
[0081] [Examples 2 to 9 and Comparative Examples 1 to 5] Similarly to Example 1, heat-shrinkable foamed films of Examples 2 to 9 and Comparative Examples 1 to 5 were prepared according to Tables 3 and 4. The physical properties and evaluations of the heat-shrinkable foamed films are shown in Tables 3 and 4.
[0082] [Table 3]
[0083] [Table 4] [Explanation of symbols]
[0084] 1: Foam layer 3, 4: Non-foamed layer 5, 6: Adhesive layer (undercoat layer)
Claims
1. A foamed film comprising a foamed layer and one or more non-foamed layers, The first resin composition constituting the foam layer is One or more block copolymers having vinyl aromatic hydrocarbon monomer units and conjugated diene monomer units, The melt mass flow rate at 200°C and a load of 5 kg is 5.0 to 15.0 g / 10 min; The second resin composition constituting the non-foamed layer is One or more block copolymers having vinyl aromatic hydrocarbon monomer units and conjugated diene monomer units, The melt mass flow rate at 200°C and a load of 5 kg is 2.0 to 7.0 g / 10 min; The specific gravity of the foamed film is 0.8 or more and less than 1.0, At least one non-foamed layer is provided as a surface layer. Foam film.
2. The foamed film according to claim 1 , wherein the first resin composition has a melt mass flow rate at 200° C. under a load of 5 kg that is greater than the melt mass flow rate of the second resin composition at 200° C. under a load of 5 kg.
3. The foamed film according to claim 1 or claim 2, wherein the first resin composition and / or the second resin composition has a conjugated diene monomer unit content of 10 to 40 mass%, when the total of the vinyl aromatic hydrocarbon monomer unit and the conjugated diene monomer unit in each composition is 100 mass%.
4. A heat shrinkable film using the foamed film according to any one of claims 1 to 3.
5. A label using the foamed film according to any one of claims 1 to 3 or the heat-shrinkable film according to claim 4.
Citation Information
Patent Citations
JP1973013181B1
Sheet for forming sleeve
JP1984029152A
Sheet for forming shrinkable sleeve
JP1985131235A
Heat-shrinkable composite foamed resin film
JP1986025834A
Sheet for forming shrinkable sleeve
JP1989093341A